The structure of competence: Evaluating the factor structure of the Cognitive Therapy Rating Scale - Goldberg, Simon B. (Behav Ther, 2019)
The Cognitive Therapy Rating Scale (CTRS) is an observer-rated measure of cognitive behavioral therapy (CBT) treatment fidelity. Although widely used, the factor structure and psychometric properties of the CTRS are not well established. Evaluating the factorial validity of the CTRS may increase its utility for training and fidelity monitoring in clinical practice and research. The current study used multilevel exploratory factor analysis to examine the factor structure of the CTRS in a large sample of therapists (n = 413) and observations (n = 1264) from community-based CBT training. Examination of model fit and factor loadings suggested that three within-therapist factors and one between-therapist factor provided adequate fit and the most parsimonious and interpretable factor structure. The three within-therapist factors included items related to (a) session structure, (b) CBT-specific skills and techniques, and (c) therapeutic relationship skills, although three items showed some evidence of cross-loading. All items showed moderate to high loadings on the single between-therapist factor. Results support continued use of the CTRS and suggest factors that may be a relevant focus for therapists, trainers, and researchers.